2003
DOI: 10.1242/jeb.00178
|View full text |Cite
|
Sign up to set email alerts
|

Putative involvement of crustacean hyperglycemic hormone isoforms in the neuroendocrine mediation of osmoregulation in the crayfishAstacus leptodactylus

Abstract: This study investigates the involvement of eyestalk neuroendocrine factors on osmoregulation in the crayfishAstacus leptodactylus maintained in freshwater. Eyestalk removal was followed by a significant decrease in hemolymph osmolality and Na + concentration and by a 50% increase in mass after one molting cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
68
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 54 publications
6
68
0
Order By: Relevance
“…Yasuda et al (Yasuda et al, 1994) applied the two isomers to in vitro incubated Y-organs, the molting hormone-producing organ, from P. clarkii and noticed about 10-times stronger inhibition of molting hormone synthesis by D-CHH than by the L-isomer. Serrano et al (Serrano et al, 2003) demonstrated that, in P. leptodactylus, a more prominent increase of osmolarity and sodium concentration in the circulation was caused by D-CHH than by L-CHH. Finally, a different time course and intensity of increase in circulating glucose was triggered by the two isomers in P. leptodactylus (Lebaupain et al, 2012;Mosco et al, 2012;Serrano et al, 2003).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Yasuda et al (Yasuda et al, 1994) applied the two isomers to in vitro incubated Y-organs, the molting hormone-producing organ, from P. clarkii and noticed about 10-times stronger inhibition of molting hormone synthesis by D-CHH than by the L-isomer. Serrano et al (Serrano et al, 2003) demonstrated that, in P. leptodactylus, a more prominent increase of osmolarity and sodium concentration in the circulation was caused by D-CHH than by L-CHH. Finally, a different time course and intensity of increase in circulating glucose was triggered by the two isomers in P. leptodactylus (Lebaupain et al, 2012;Mosco et al, 2012;Serrano et al, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…Serrano et al (Serrano et al, 2003) demonstrated that, in P. leptodactylus, a more prominent increase of osmolarity and sodium concentration in the circulation was caused by D-CHH than by L-CHH. Finally, a different time course and intensity of increase in circulating glucose was triggered by the two isomers in P. leptodactylus (Lebaupain et al, 2012;Mosco et al, 2012;Serrano et al, 2003). Earlier hyperglycemia was induced by L-CHH but it lasted for a shorter period and was less intensive than that induced by D-CHH.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In recent years, a variety of other functions for these hormones have been established, involving (for example) inhibition of ecdysteroid (Webster and Keller, 1986;Chang et al, 1990;Chung and Webster, 2003;Chung and Webster, 2005), methyl farnesoate (Liu et al, 1997) and ovarian protein synthesis (Khayat et al, 1998;Avarre et al, 2001). A subject of topical interest is the involvement of CHH in ionoregulatory processes (Charmantier-Daures et al, 1994;Charmantier et al, 1999;Chung et al, 1999;Townsend et al, 2001;Serrano et al, 2003;Chung and Webster, 2006). Whilst it is known that sinus gland extracts cause rapid and reversible changes in transepithelial potentials, and Na + transport in isolated perfused gills of Pachygrapsus marmoratus (Spanings-Pierrot et al, 2000), the precise mechanisms regulated by CHH in crustacean gill tissues remain poorly investigated, despite our extensive knowledge of branchial membrane exchangers and pumps (Lucu, 1990;Onken et al, 1991;Onken and Putzenlechner, 1995;Lucu and Towle, 2003;Weihrauch et al, 2004;Tsai and Lin, 2007;Masui et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These include the repression of ecdysteroid synthesis by the Y-organ, and thus a possible involvement in moult control (Webster and Keller, 1986;Chang et al, 1990), the inhibition of reproductive processes via the inhibition of methyl farnesoate synthesis (Liu et al, 1997), and the inhibition of vitellogenin (Vg) mRNA, protein synthesis (Khayat et al, 1998) or Vg gene expression (Tsutsui et al, 2005). An involvement in iono-osmoregulatory processes is also documented (Charmantier-Daures et al, 1994;Chung et al, 1999;Serrano et al, 2003), and it appears that CHH is involved in stimulation of ion transport across respiratory epithelia (SpaningsPierrot et al, 2000) and in dipsogenesis during ecdysis (Chung et al, 1999).…”
Section: Introductionmentioning
confidence: 99%